IMPROVING LISTENING SKILLS BY PODCASTS - Suyunova Mohinur Ilhom qizi (International Journal on Integrated Education, 2022)
Being a receptive skill, listening is often ignored in level EAP (English for academic purpose) classrooms. Even though the prominence remains mostly on writing and speaking, developing listening comprehension is equally significant for EAP learners. One effective way of practicing listening skills is to use podcasts in the classroom. Many research findings imply that podcasts provide flexibility among young learners as well as offer a wide range of content to real-life listening. This paper, therefore, sheds light on the usefulness of using podcasts to develop listening skills in tertiary classrooms in the light of existing literature. The study suggests that podcasts can be an effective means to practice extensive listening skills. However, the teachers need to pay particular attention to choose content and make the overall learning process enjoyable for the learners.